1921 Mo. Laws 693, § 4 - (:unkn) unknown (My University, 1921)
Weapons, Firearms: Regulation of Sale and Possession, § 4: Nothing herein contained shall be considered or construed as forbidding or making it unlawful for a dealer in or manufacturer of pistols, revolvers or other firearms of a size which may be concealed upon the person, located in this state, to ship into other states or foreign countries, any such articles whether stamped as required by this act or not so stamped.
Keywords: COMMERCIAL SALES REGULATION